STUDI PERILAKU CHEATING SISWA MADRASAH DAN SEKOLAH ISLAM KETIKA UJIAN NASIONAL - Kusaeri, Kusaeri (Program Studi Pendidikan Agama Islam, 2016)
THE STUDY OF MADRASA AND ISLAMIC SCHOOL STUDENTS’ CHEATING BEHAVIOR IN NATIONAL EXAMINATION. This study describes the cheating occurred in Madrasah/Islamic High Schools in East Java. It is based on the achievement of UN and IIUN 2015. It used descriptive approach. The data were presented in narrative, percentage, tables, graphs, and charts. Data were obtained from Center of Education Assessment, Balitbang Kemendikbud. East Java was chosen because it is province with highest number (1,117) from 6.608 Madrasah/Islamic High Schools in Indonesia. The data were analysed using encoding, recording, diagraming, and statistical calculations. Cheating index was determined using the Pair Wise and Cumulative Method. The results show that 5.26% of Madrasah/Islamic High School students reached the graduation criteria (UN score above 55) with IIUN more than 70. Contrastly, 40% of Christian/Catholic High Schools students obtained UN score above 55 with IIUN more than 70. These results illustrate the cheating among Madrasah/Islamic High School students in East Java is higher than Christian/Catholic High School students.